2005
DOI: 10.4049/jimmunol.175.11.7496
|View full text |Cite
|
Sign up to set email alerts
|

A Model Vaccine Exploiting Fungal Mannosylation to Increase Antigen Immunogenicity

Abstract: Ag mannosylation represents a promising strategy to augment vaccine immunogenicity by targeting Ag to mannose receptors (MRs) on dendritic cells. Because fungi naturally mannosylate proteins, we hypothesized that Ags engineered in fungi would have an enhanced capacity to stimulate T cell responses. Using the model Ag OVA, we generated proteins that differentially expressed N- and O-linked mannosylation in the yeast Pichia pastoris and compared them to their unglycosylated counterparts produced in Escherichia c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
93
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(96 citation statements)
references
References 48 publications
3
93
0
Order By: Relevance
“…In mice, bone marrow-derived DCs were shown to internalize Ag through the MR for presentation to T cells, although MR ligands were not presented as efficiently as ligands for DEC-205, another member of the MR family of proteins (18), and MR expression is required for cross-presentation of the soluble model Ag OVA (19). In contrast, Napper and Taylor recently reported that fibroblasts cotransfected with the MR and MHCII were not able to enhance the presentation of glycosylated Ag to T cells (20), and Ags engineered in fungi to enhance mannosylation elicit T cell responses independently of the MR (21).…”
Section: Endritic Cells (Dcs)mentioning
confidence: 99%
“…In mice, bone marrow-derived DCs were shown to internalize Ag through the MR for presentation to T cells, although MR ligands were not presented as efficiently as ligands for DEC-205, another member of the MR family of proteins (18), and MR expression is required for cross-presentation of the soluble model Ag OVA (19). In contrast, Napper and Taylor recently reported that fibroblasts cotransfected with the MR and MHCII were not able to enhance the presentation of glycosylated Ag to T cells (20), and Ags engineered in fungi to enhance mannosylation elicit T cell responses independently of the MR (21).…”
Section: Endritic Cells (Dcs)mentioning
confidence: 99%
“…Uptake of antigens via these receptors on the APC surface is followed by delivery into the endolysosomal pathway, leading to MHC-class II presentation [4]. In comparison to antigens internalized via the fluid phase (e.g., pinocytosis), this pathway of antigen uptake in DC results in a considerable increase of efficiency in antigen presentation and T cell stimulation [5][6][7][8]. For instance, it was shown that antigen uptake mediated by mannosebinding receptors increased antigen presentation to T cells up to 100-fold [5].…”
Section: Introductionmentioning
confidence: 99%
“…Mannosylated antigens were efficiently internalized by DC and localized in the MHC class II-specific compartments and lysosomes, resulting in 200-10 000-fold enhanced potency in stimulating specific MHC class II-restricted T cells [8]. Yeast-derived recombinant OVA antigens that contained branched N-and O-linked mannose were far more immunogenic than non-mannosylated OVA [6]. Extensive O-mannosylation of proteins greatly enhanced antigen delivery, and deglycosylation profoundly inhibited T cell responses [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When formulating recombinant fungal vaccines, special consideration must also be given to the method chosen for its synthesis, as native glycosylation is lost in bacterial expression systems. Lack of native glycosylation decreases the immunogenicity of some fungal proteins (Lam et al 2005;Levitz and Specht 2006;Specht et al 2007). …”
Section: Recombinant Protein Vaccinesmentioning
confidence: 99%